2020
DOI: 10.3847/2041-8213/abad28
|View full text |Cite
|
Sign up to set email alerts
|

Different Fates of Young Star Clusters after Gas Expulsion

Abstract: We identify structures of the young star cluster NGC 2232 in the solar neighborhood (323.0 pc) and a newly discovered star cluster, LP 2439 (289.1 pc). Member candidates are identified using the Gaia DR2 sky position, parallax, and proper-motion data by an unsupervised machine-learning method, StarGO. Member contamination from the Galactic disk is further removed using the color–magnitude diagram. The four identified groups (NGC 2232, LP 2439, and two filamentary structures) of stars are coeval with an age of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 61 publications
5
53
0
Order By: Relevance
“…We modified the prior with respect to A13 to take into account the recent results of e.g., Meingast, Alves, & Rottensteiner (2021): from a sample of young open clusters with ages between 30 and 300 Myr (perfectly matching the ages of Cepheids), they found that almost all clusters are surrounded by a large halo a stars they call coronae and which extend further than 100 pc from the clusters' centre. Most clusters show evidences of expansion along one or more spatial axes, a feature also observed by, e.g., Pang et al (2020). Although reminiscent of tidal features observed in older clusters, such features are most likely primordial and related to filamentary star formation (e.g., Beccari, Boffin, & Jerabkova 2020;Tian 2020).…”
Section: On-sky Selection and Prior 𝑃( 𝐴)mentioning
confidence: 73%
“…We modified the prior with respect to A13 to take into account the recent results of e.g., Meingast, Alves, & Rottensteiner (2021): from a sample of young open clusters with ages between 30 and 300 Myr (perfectly matching the ages of Cepheids), they found that almost all clusters are surrounded by a large halo a stars they call coronae and which extend further than 100 pc from the clusters' centre. Most clusters show evidences of expansion along one or more spatial axes, a feature also observed by, e.g., Pang et al (2020). Although reminiscent of tidal features observed in older clusters, such features are most likely primordial and related to filamentary star formation (e.g., Beccari, Boffin, & Jerabkova 2020;Tian 2020).…”
Section: On-sky Selection and Prior 𝑃( 𝐴)mentioning
confidence: 73%
“…Self-organizing maps have already found wide application in astronomy, especially when dealing with large multidimensional data sets. They have been applied: to light curves of variable stars (Brett et al 2004;Armstrong et al 2016); as an aid in the context of photometric redshift estimation (Geach 2012;Masters et al 2015); to cluster gamma-ray bursts (Rajaniemi & Mähönen 2002); for morphological classification of galaxies (Naim et al 1997); to find star clusters or otherwise coherent structures in Gaia data (Yuan et al 2018(Yuan et al , 2020Pang et al 2020); to find anomalous data in SDSS spectra (Fustes et al 2013;Meusinger & Balafkan 2014); to find variable active galactic nuclei (Faisst et al 2019), and so on.…”
Section: General Informationmentioning
confidence: 99%
“…For example, the value of the SFE, initial cluster radii, the time-scale of gas expulsion and the degree of primordial mass segregation are subject to ongoing research (e.g. Er et al 2013;Kuhn et al 2014;Banerjee & Kroupa 2015;Megeath et al 2016;Spera & Capuzzo-Dolcetta 2017;Domínguez et al 2017;Pfalzner 2019;Kuhn et al 2019;Dib & Henning 2019;Pang et al 2020). Some of the cluster initial conditions are interrelated: for example, embedded star clusters cannot form with sub-parsec scales and SFE close to 100% because they would not be able to expand to their observed sizes (Banerjee & Kroupa 2017).…”
Section: The Influence Of the Initial Conditions Of Star Clustersmentioning
confidence: 99%